Expanding pharmacy support in rural areas: views from rural healthcare providers in Queensland - Tan, A.; Emmerton, Lynne; Hattingh, Laetitia (Pharmaceutical Society of Australia, 2012)
Introduction: The limited rural pharmacy workforce may hinder provision of medication support or pharmacy specialty services in rural areas. To date, well-established capacity-building initiatives to improve service provision in rural areas include alternative delivery models, such as sessional employment, outreach services and telehealth. This paper explores service delivery models involving pharmacists and roles for pharmacy support staff, from the perspectives of rural healthcare providers in a study community in Queensland. Methods: A rural community comprising four towns, and the healthcare providers servicing this community, were identified within a Health Service District in Queensland. Medical practitioners (n=5), pharmacists (n=7), intern pharmacists (n=2) and hospital registered nurses (n=11) participated in semi-structured face-to-face interviews. The interviews explored a range of topics, including rural medication support and service models. Interviews (averaging 45 minutes in duration) were recorded, transcribed and manually analysed for breadth of responses. Results: While sessional employment, outreach services and tele-pharmacy were not practised in this community at the time of the study, participants reflected on the benefits and challenges of providing clinical consultation and medication support through these means, based on their practice experiences elsewhere. Funding was identified as a significant barrier to implementing these services. Rural practitioners also supported potential role extension for pharmacy support staff into medication supply. Conclusions: The potential to explore service models was recognised in this rural community, with outcomes informing stakeholders and policymakers, and possibly generating novel career paths for rural pharmacists and pharmacy support staff.